Fundamentals of Entrepreneurship ENT300 Ti'ke Freshwater Fish / Vincent Arnold Soueng... [et al.] - Soueng, Vincent Arnold; Nelson, Melissa Fiona; Othman, Muhammad Haziq; Mahmud, Mohd Nazri; Yusof, Nur Izni Liyana (2019)
As we agreed before, all the shareholders in our company have decided the name of our company is Ti Ke Freshwater Fish. We have decided to form our business in partnership form which consists of five shareholders. Our company main activities are selling fresh and frozen tilapia and catfish. Our business located at 1234, Jalan Matang Batu 8, 93050 Kuching, Sarawak. In this business, each of the shareholders will have the responsibility to perform their own job and task that has been given. This is important for the company to gain the maximum profit thus to achieve our mission and vision. In addition, we are concern about the quality of our product and services among the organization and customers. As this business is in a partnership form, all shareholders had agreed that Vincent Arnold anak Soueng as the General Manager. The Administration Manager is Mohd Nazri bin Mahmud, Melissa Fiona anak Nelson as the Marketing Manager, Muhammad Haziq bin Othman as the Operation Manager and lastly Nur Izni Liyana binti Yusof as the Financial Manager. The General Manager is responsible to make a decision of the company, make sure all managers do their work, and make a short-term and long-term planning of the company. The Administration Manager will indicate the company’s structure and key talents. Meanwhile, the Operation Manager will control the operation of our business while the Marketing Manager is responsible in preparing the market plan that includes the target market and sales forecast. Lastly, our Financial Manager will handle all the financial such as preparing budget and financial statement for the company.